2021
DOI: 10.1017/etds.2021.68
|View full text |Cite
|
Sign up to set email alerts
|

A non-Borel special alpha-limit set in the square

Abstract: We consider the complexity of special $\alpha $ -limit sets, a kind of backward limit set for non-invertible dynamical systems. We show that these sets are always analytic, but not necessarily Borel, even in the case of a surjective map on the unit square. This answers a question posed by Kolyada, Misiurewicz, and Snoha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…All of this, applied to the right hand side of ≤ in (17), shows that (18) D(E(y, j), µ n(j) ) → 0 as j → ∞.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…All of this, applied to the right hand side of ≤ in (17), shows that (18) D(E(y, j), µ n(j) ) → 0 as j → ∞.…”
Section: Resultsmentioning
confidence: 96%
“…Also, sets of interest in dynamics are sometimes complete at levels past the Borel hierarchy. For example, in [17] a dynamical system in the unit square is constructed for which the set of special α-limit points is Π 1 1complete.…”
Section: Introductionmentioning
confidence: 99%
“…Outside the realm of one-dimensional dynamics the situation is even more complicated. It has been shown that sα-limit sets are always analytic, but not necessarily closed or even Borel [17,18]. Therefore it seems prudent to study more closely the properties of sα-limit sets in onedimensional dynamics, and especially in the most important one-dimensional space where Hero's work began, the unit interval.…”
Section: Introductionmentioning
confidence: 99%
“…Outside the realm of one-dimensional dynamics the situation is even more complicated. It has been shown that sα-limit sets are always analytic, but not necessarily Borel [22]. If we denote by SA(f ) (respectively, ω(f )) the union of α-limit sets of all backward branches (respectively, all ω-limit sets) of a map f and by Rec(f ) the set of all recurrent points of f , then Rec(f ) ⊆ SA(f ) ⊆ Rec(f ) ⊆ ω(f ), for every map f on the topological graph (see [34], cf.…”
mentioning
confidence: 99%